The Effect of Control Corruption, Political Stability, Macroeconomic Variables on Asian Economic Growth - Khubbi Abdillah; Rossanto Dwi Handoyo; Wasiaturrahma Wasiaturrahma (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to analyze the correlation between control corruption and political stability, macro variables on economic growth in Asia. Study population consist of 47 countries, employing secondary data from Worldwide Governance Indicators, World Development Indicators, and United Nations Development Programme. The data were analyzed using dynamic panelÂ regression (GMM) during 2002-2018 period with Stata 14 software. The result of the analysis shows control corruption and political stability positively affect economic growth. Macroeconomic variables consist of foreign direct investment and human capital positively affects economic growth. While government size has no significant effect on economic growth. The findings of this study confirms that economic growth can be increased through reducing levels of corruption, strong political stability, increase capital inflow, optimally government consumption especially increasing portion of the education budget and creating jobs widely.